2012
DOI: 10.1039/c2sm26313k
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between elastic instabilities and shear-banding: three categories of Taylor–Couette flows and beyond

Abstract: In the past twenty years, shear-banding flows have been probed by various techniques, such as rheometry, velocimetry and flow birefringence. In micellar solutions, many of the data collected exhibit unexplained spatiotemporal fluctuations. Recently, it has been suggested that those fluctuations originate from a purely elastic instability of the shear-banding flow. In cylindrical Couette geometry, the instability is reminiscent of the Taylor-like instability observed in viscoelastic polymer solutions. The crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 106 publications
(373 reference statements)
3
68
1
Order By: Relevance
“…The same procedure was performed for rates 10 s −1 , 12 s −1 , and 18 s −1 for the smooth wall and for Other values forγ a did not show any regular oscillation pattern and a wavelength extraction was not possible. In the case where a wavelength could be determined, it can be stated that the results are above the predictions (following Fardin et al (2012b)) by about a factor of two and that the wavelength is increasing for higher applied shear rates. The increase may be interpreted as linear, however, only four data points are available.…”
Section: Higher Dimensions: Vorticity Undulations and Temporal Fluctumentioning
confidence: 91%
See 2 more Smart Citations
“…The same procedure was performed for rates 10 s −1 , 12 s −1 , and 18 s −1 for the smooth wall and for Other values forγ a did not show any regular oscillation pattern and a wavelength extraction was not possible. In the case where a wavelength could be determined, it can be stated that the results are above the predictions (following Fardin et al (2012b)) by about a factor of two and that the wavelength is increasing for higher applied shear rates. The increase may be interpreted as linear, however, only four data points are available.…”
Section: Higher Dimensions: Vorticity Undulations and Temporal Fluctumentioning
confidence: 91%
“…The structure is reminiscent of Taylor-Couette vortices and has already been observed for over 20 years in the case of polymeric fluids (Larson et al 1990). A more thorough study (Fardin et al 2012b) found that the wavelength of the undulations scales linearly with the size of the high shear rate band, which is usually in the order of the gap width. In contrast, Feindel and Callaghan (2010) observed structures in vorticity direction in the order of centimeters.…”
Section: Higher Dimensions: Vorticity Undulations and Temporal Fluctumentioning
confidence: 92%
See 1 more Smart Citation
“…While inertia is at the heart of flow instabilities in simple fluids, non-Newtonian fluids, such as polymer or self-assembled surfactant solutions, may display instabilities at vanishingly small Reynolds numbers due to elasticity [7,8] or due to a strong coupling between the flow and the fluid microstructure [9]. A typical example is provided by wormlike micellar solutions where shear-induced alignment associated with high viscoelasticity leads to shear-banded flows that transition to elastic turbulence at high Weissenberg numbers [10].…”
Section: Introductionmentioning
confidence: 99%
“…They expanded the parameter regime studied by systematically tuning the surfactant concentration of the solutions [33], and elucidated the interplay between elastic instabilities and shear-banding. More recently, they tested an even more diluted non-shear-banding wormlike micellar solution (CTAB/NaNO 3 [0.1:0.3] M) [34].…”
Section: Introductionmentioning
confidence: 99%